Evaluation of thermal bioconvective phenomenon for periodically accelerating nonlinear radiated flow of Maxwell nanofluid with triple diffusion effects - Sami Ullah Khan; Shanza Bibi; Aqsa Bibi; Adnan; Khalid B. Saleem; Badr M. Alshammari; Rejab Hajlaoui; Lioua Kolsi (Alexandria Engineering Journal, 2024)
Due to the outstanding thermal properties of nanoparticles, scientists have introduced a range of multidisciplinary applications in fields such as heat transfer systems, thermal management, solar energy, chemical processes, manufacturing, and cooling technologies. The aim of the current paper is to inspect the heat and mass transfer pattern during Maxwell nanofluid flow considering the diffusion phenomenon. The suspension of microorganisms has been considered for bioconvective flow. The inspection of heat transfer is analyzed by adopting the nonlinear radiated effects. The motivations for considering the Maxwell fluid are associated to novel relaxation time features occurring in polymer industry and manufacturing systems. The endorsed flow is caused by periodically oscillating surface with porous medium. The whole mathematical model is developed in terms of partial differential equations (PDE’s). A successful analytical solution is presented via homotopy analysis method (HAM). It is observed that solutal concentration reduces due to modified Duffer Lewis number and Deborah number. The surface heating parameter and magneto-porosity constant enhances the temperature profile. The predicted results convey significant impact in enhancing the energy reservoirs, diffusion applications, nuclear systems, oil industry, storage energy, space exploration etc.